Contribution to Knowledge of the Content of Heavy Metals (Pb, Cu, Zn and Cd) in Speleological Objects in the Risnjak National Park (Croatia) - Vrbek, Boris; Buzjak, Nenad (Acta Carsologica, 2016)
Vzorce mulja smo nabrali v šestih jamah v Narodnem parku Risnjak v Gorskem kotarju. Da bi kar najbolj omejili neposreden antropogeni vpliv, smo vzorčili v težko dostopnih razpokah in breznih. Vzorce smo pedološko analizirali in jim izmerili vsebnost težkih kovin. Rezultati so pokazali nizko vsebnost svinca, bakra in cinka, ki je nižja kot v večini hrvaških jam, medtem ko je vsebnost kadmija višja kot v drugih jamah. Vsebnost težkih kovin v jamah je nižja kot v humusnem horizontu. Samples of silt were taken from six speleological objects in the Risnjak National Park in Gorski kotar area (NW Croatia). The samples were taken from almost inaccessible rock fissures and shafts in order to find the most natural sediment outside the reach of anthropogenic pollution. The samples were examined in the Laboratory of the Forest Research Institute, where standard pedological analyses were performed, and the content of several heavy metals (Pb, Cu, Zn and Cd) was determined. The results indicate relatively low values of the content of lead, copper and zinc, while the values of cadmium in the sediment were increased above the limit level of 2 mgkg-1 in the majority of speleological objects. The content of other heavy metals (Pb, Cu and Zn) in mgkg-1 was lower than previously determined in samples taken from other speleological objects on the Croatian territory. Also, the content of heavy metals was lower in relation to surface soil samples taken from the humus horizon and mineral part of the soil under the parent rock of limestone, when sampling the soils of the Risnjak National Park.